PEMANFAATAN LIMBAH DENIM UNTUK PERANCANGAN STREETWEAR WANITA MENGGUNAKAN TEKNIK INTERLOCKING MODULAR DAN LASER CUT - Salsabil, Zafira Salma; Tanzil, Marini Yunita; Tahalele, Yoanita Kartika Sari (Universitas Ciputra Surabaya, 2025)
The fashion industry, particularly the denim sector, is experiencing rapid growth in Indonesia but also causes significant environmental problems due to poorly managed production waste. This research aims to reduce environmental pollution by utilizing denim waste through interlocking modular and laser cut techniques in the design of women's streetwear. The interlocking modular technique allows the combination of denim fabric modules into strong and aesthetically pleasing structures, while laser cutting is used to precisely cut decorative motifs. This method is developed based on techniques previously applied by Eunsuk Hur. This study employs a qualitative method through interviews with six experts and twelve extreme users, along with observations, literature reviews, journals, and articles. The results indicate that the combination of interlocking modular and laser cut techniques can produce visually appealing women's streetwear collections while reducing fashion industry waste. In the initial stages, denim modules used in the interlocking modular technique were not lined with interfacing, making them prone to damage even after using the laser cut technique. The study found that adding interfacing is crucial to prevent fiber damage. Denim, being a material that is quite challenging to process using the interlocking modular technique, requires in-depth experimentation to adjust methods to achieve the desired aesthetic and functional outcomes. Overall, this research provides valuable insights into experimental approaches in sustainable fashion design. By continuously experimenting and involving users in the development process, it is hoped that this innovation can inspire the local fashion industry to be more mindful of denim waste utilization and support environmental sustainability.